Composition of chemical elements in the biosubstrate (hair) of children of the Karaganda region - Nurlybaeva, K.A.; Aitkulov, A.M.; Mukasheva, G. Zh.; Tykezhanova, G.M. (KU Publ., 2021)
In the article we studied chemical elements in the hair of children as a form of environmental monitoring of metals in a given area, since one of the objective indicators of the ecological and hygienic well-being of a territory is the status of trace elements as the most sensitive part of the population, especially children. Many foreign scientific studies have shown that a hair sample is a good indicator of a negative technogenic impact on humans, and it is known that the unfavorable state of children characterizes the ecogeochemical features of the area, so we took into account the accumulation of trace elements in the hair. The study showed an increase in lead and cadmium and a decrease in zinc, copper and chromium.
Қарағанды облысы балаларының биосубстратындағы (шаштарындағы) химиялық элементтердің құрамы
Состав химических элементов в биосубстрате (волосах) детей Карагандинской области
Keywords: children; health; heavy metals; hair; toxic trace elements; chromium; zinc; manganese